(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
This study investigated the factor structure of readiness constructs as expressed by undergraduate students and examined how these constructs correlated with some selected socio-demographic characteristics at the Business School of a Malaysian private university. Results were based on responses from 172 undergraduate students who were exposed to some kind of e-learning activities. The 13-item questionnaire used was adapted from The Readiness for Online Learning Survey by McVay (2001). Exploratory Factor Analysis yielded four aspects of motivation that described themes of self-study management, reflective thinking, interaction support and learning setting. The similarities and differences between this study and past researches were discussed.